Evaluation of agility and acceleration levels in male and female futsal players - Samet Aktaş (Turkish Journal of Kinesiology, 2023)
The aim of this study is to reveal the direction and level of the relationship between acceleration and agility in university student female and male futsal players who play futsal as amateurs. The subject group of the research consists of 15 male and 15 female university students who play futsal in the amateur league and practice futsal at least 3 days a week. The mean age of the participants was 19.80 ± 1.056 years in men, 20.33 ± 2.49 years in women, mean height in men 175.80±2.45 cm, in women 164.26 ± 4.39 cm, mean body weight in men 67.60 ± 6.05 and 54.20 ± 5.10 kg for women. The T-test was used to determine the agility performances of the subjects, and the acceleration measurements were applied with a photocell placed at 5 m, 10 m, and 20 m intervals. In both parameter measurements, the values were recorded in seconds. Measured values were given as mean and standard deviation and correlation analyses were applied to the relationship between agility and acceleration. In the relationship between agility and acceleration, it was determined that there was a positive relationship between agility and 5 m, 10 m, and 20m acceleration values in males and that there was a strong positive correlation between agility and 10m acceleration (r=0.848; p=0.00). On the other hand, it is seen that there is a negative and insignificant relationship between agility and acceleration parameters in females. While there was a difference in men's agility levels in height grouping, a significant difference was found in 10m and 20m acceleration levels in female futsal players It shows that it has a negative effect on female futsal players, albeit at a low level. Since the planning of speed and acceleration exercises together with agility in training will be effective in increasing the performance of the athlete, it is recommended to include such training in training programs.